Protection of Corneal Limbus from Riboflavin Prevents Epithelial Stem Cell Loss after Collagen Cross-Linking - Hyo Kyung Lee; Jin Suk Ryu; Hyun Jeong Jeong; Mee Kum Kim; Joo Youn Oh (Journal of Ophthalmology)
Purpose. To investigate whether the protection of corneal limbus from riboflavin exposure during collagen cross-linking (CXL) prevents limbal epithelial stem cell (LESC) loss. Methods. Ten New Zealand white rabbits received an epithelium-off CXL using an accelerated protocol. Seven days before procedure, 5-bromo-2-deoxyuridine (BrdU) was intraperitoneally injected. During procedure, riboflavin was applied to the corneal surface within a 9 mm diameter retention ring in 5 rabbits, thereby preventing the limbus from riboflavin exposure. In other 5 rabbits, riboflavin was instilled every 2 min, allowing the spillover to the limbus. One day after UVA irradiation, corneas were subjected to histological and molecular assays. Results. There were no differences in corneal thickness and epithelial healing between the groups. The numbers of BrdU-labelled and p63+ limbal epithelial cells were markedly reduced in the group without a ring, but significantly increased when a ring was used. Robust expression of CK3/12 was observed in the limbal epithelium in the group with a ring. The mRNA levels of ABCG2, FGF2, IL-1β, and IL-6 were significantly increased in the corneas with a ring. Conclusions. Protection of limbus from riboflavin during CXL was effective in preserving LESCs. However, inflammation was increased in the cornea treated with riboflavin using a ring.